If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -3)(x + 8) = 0 Reorder the terms: x(-3 + x)(x + 8) = 0 Reorder the terms: x(-3 + x)(8 + x) = 0 Multiply (-3 + x) * (8 + x) x(-3(8 + x) + x(8 + x)) = 0 x((8 * -3 + x * -3) + x(8 + x)) = 0 x((-24 + -3x) + x(8 + x)) = 0 x(-24 + -3x + (8 * x + x * x)) = 0 x(-24 + -3x + (8x + x2)) = 0 Combine like terms: -3x + 8x = 5x x(-24 + 5x + x2) = 0 (-24 * x + 5x * x + x2 * x) = 0 (-24x + 5x2 + x3) = 0 Solving -24x + 5x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-24 + 5x + x2) = 0 Factor a trinomial. x((-8 + -1x)(3 + -1x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 3
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {0, -8, 3}
| 4*2-y=0 | | 7(w-5)=28 | | 3x-5=3-7 | | 8(x-5)(x+5)=0 | | 4*1-y=0 | | (3a+8b)(-6)= | | 4*0-y=0 | | -4+6=10 | | 5m+3=19 | | 3(3x^2+y^2)*dx-2xy*dy=0 | | 20log(x)=18.85 | | 5x+2x+5x+40=180 | | 2w-8=-22 | | -3/2y=6 | | 18=-6x+24 | | 11=6z+15 | | 3*2+y=-6 | | -4=6z | | 10-5p=20 | | 3*1+y=-6 | | 3*0+y=-6 | | (16x^3y^2)/(8x^6y^2) | | ln(x-3)=ln(x+17)-ln(x-1) | | -35=-4(-4y)-9(2y)+y | | -4(-4y)-9(2y)+y= | | 2+2u=-8 | | -5/2y=6 | | 3(33-3X)+1X=27 | | 2t^2-5t-25=0 | | 2f(3d+5)= | | 1+2y=-2 | | 5x/10=-25 |